Acceptance, Perceived Benefits, and Helplessness among Coronary Heart Disease Patients Undergoing Treatment in A Different Ward - Aan Nur'aeni; Ristina Mirwanti (Universitas Padjadjaran, 2020)
Background. One of the factors determining CHD patients' adherence to treatment is Illness Cognition (IC). IC is described as acceptance, perceived-benefits, and helplessness. This study aims to identify and compared IC in CHD patients treated in different wards. Method: This research used a descriptive quantitative method with a cross-sectional approach. The study population was CHD patients who were undergoing treatment at a referral hospital in West Java. Selection of respondents using consecutive sampling, and data collected within three months, using the Illness Cognition Questionnaire on 106 respondents. Data were analyzed using mean and frequency distribution. Furthermore, ICs were compared using the Kruskal Wallis Test. Results: The following are an average IC respondent based on different IC dimensions and ward. Dimensions of helplessness: High Care Cardiac Unit (HCCU) 16.1 (SD = 4.06); Regular ward 12.86 (SD = 4.95); Outpatient 14.05 (SD = 5); Cardiac-Rehabilitation (CR) 11.04 (SD = 3.52) with p = 0.013. Dimensions of acceptance: HCCU 14.00 (SD = 2.7); Regular-ward 18.26 (SD = 2.7); outpatient 19.34 (SD = 2.88); RJ 18.20 (SD = 3.47) p = 0.005. Dimensions of perceived-benefits of HCCU 18.00 (SD = 3.6); Regular-ward 19.96 (SD = 2.76); outpatient 20.95 (SD = 3.01); RJ 20.08 (SD = 3.46) p = 0.043. Conclusion: The worst ICs of all dimensions were owned by respondents who were undergoing treatment at HCCU. ICs with relatively better are seen in respondents who were undergoing treatment in outpatient and cardiac-rehabilitation. ICs in CHD patients differ in all dimensions and categories of the ward. Thus, patient acceptance at HCCU need to be increased and as well as participation in cardiac rehabilitation so that patient perceived-benefits increase.